A HISTORY OF HADRAMI COMMUNITY IN SOUTHEAST ASIA - Imam Subchi (IAIN Tulungagung, 2019)
Hadrami-Arabs have played essential roles in Islamisation process across Southeast Asian region. This article diachronically examines the history of Hadrami community and their roles in islamisation. It looks at the dynamics, adaptation, and contestation of Islamisation in the region. This article offers actors-centered accounts of how the Hadrami community contributes to Islamic proselitisation activism (dakwah), politics, and contestation within the community. It further argues that, throughout the history of Hadrami in Southeast Asia, political adaptation and contestation have been essential elements that shape the current Islamic-scape in contemporary Southeast Asia.